Pattern of hippocampal shape and volume differences in blind subjects - Leporé, Natasha; Shi, Yonggang; Lepore, Franco; Fortin, Madeline; Voss, Patrice; Chou, Yi-Yu; Lord, Catherine; Lassonde, Maryse; Dinov, Ivo D.; Toga, Arthur W.; Thompson, Paul M. (NeuroImage (Orlando, Fla.), 2009)
Numerous studies in animals and humans have shown that the hippocampus (HP) is involved in spatial navigation and memory. Blind subjects, in particular, must memorize extensive information to compensate for their lack of immediate updating of spatial information. Increased demands on spatial cognition and memory may be associated with functional and structural HP plasticity. Here we examined local size and shape differences in the HP of blind and sighted individuals. A 3D parametric mesh surface was generated to represent right and left HPs in each individual, based on manual segmentations of 3D volumetric T1-weighted MR images of 22 blind subjects and 28 matched controls. Using a new surface mapping algorithm described in (Shi, Y., Thompson, P.M., de Zubicaray, G.I., Rose, S.E., Tu, Z., Dinov, I., Toga, A.W., Direct mapping of hippocampal surfaces with intrinsic shape context, NeuroImage, Available online May 24, (In Press).), we created an average hippocampal surface for the controls, and computed its normal distance to each individual surface. Statistical maps were created to visualize systematic anatomical differences between groups, and randomization tests were performed to correct for multiple comparisons. In both scaled and unscaled data, the anterior right HP was significantly larger, and the posterior right HP significantly smaller in blind individuals. No significant differences were found for left HP. These differences may reflect adaptive responses to sensory deprivation, and/or increased functional demands on memory systems. They offer a neuroanatomical substrate for future correlations with measures of navigation performance or functional activations related to variations in cognitive strategies.